Polypyridylruthenium(II) complexes exert anti-schistosome activity and inhibit parasite acetylcholinesterases. - Madhu K Sundaraneedi; Bemnet A Tedla; Ramon M Eichenberger; Luke Becker; Darren Pickering; Michael J Smout; Siji Rajan; Phurpa Wangchuk; F Richard Keene; Alex Loukas; J Grant Collins; Mark S Pearson (Public Library of Science (PLoS), 2017)
Schistosomiasis affects over 200 million people and there are concerns whether the current chemotherapeutic control strategy (periodic mass drug administration with praziquantel (PZQ)-the only licenced anti-schistosome compound) is sustainable, necessitating the development of new drugs.We investigated the anti-schistosome efficacy of polypyridylruthenium(II) complexes and showed they were active against all intra-mammalian stages of S. mansoni. Two compounds, Rubb12-tri and Rubb7-tnl, which were among the most potent in their ability to kill schistosomula and adult worms and inhibit egg hatching in vitro, were assessed for their efficacy in a mouse model of schistosomiasis using 5 consecutive daily i.v. doses of 2 mg/kg (Rubb12-tri) and 10 mg/kg (Rubb7-tnl). Mice treated with Rubb12-tri showed an average 42% reduction (P = 0.009), over two independent trials, in adult worm burden. Liver egg burdens were not significantly decreased in either drug-treated group but ova from both of these groups showed significant decreases in hatching ability (Rubb12-tri-68%, Rubb7-tnl-56%) and were significantly morphologically altered (Rubb12-tri-62% abnormal, Rubb7-tnl-35% abnormal). We hypothesize that the drugs exerted their activity, at least partially, through inhibition of both neuronal and tegumental acetylcholinesterases (AChEs), as worms treated in vitro showed significant decreases in activity of these enzymes. Further, treated parasites exhibited a significantly decreased ability to uptake glucose, significantly depleted glycogen stores and withered tubercules (a site of glycogen storage), implying drug-mediated interference in this nutrient acquisition pathway.Our data provide compelling evidence that ruthenium complexes are effective against all intra-mammalian stages of schistosomes, including schistosomula (refractory to PZQ) and eggs (agents of disease transmissibility). Further, the results of this study suggest that schistosome AChE is a target of ruthenium drugs, a finding that can inform modification of current compounds to identify analogues which are even more effective and selective against schistosomes.